Effect of cavity depth on dentine sensitivity in man - Sitthichai Wanachantararak (2018)
© 2016 Published by Elsevier Ltd. Objective To determine if dentine at the enamel-dentine junction (EDJ) in man is more sensitive to hydrostatic pressure stimuli then deeper dentine. Design Cavities (1 mm diam.) were cut at the tips of the buccal and lingual cusps of 8 premolars in 3 subjects (ages: 22-25 years). Both cavities were initially deepened to expose the EDJ then one (the test cavity) was deepened in steps of 0.5 mm to a maximum of 2.0 mm below the EDJ. The cavities were tested at each stage, before and after etching, with 5 s, hydrostatic pressure stimuli between 400 mm above, and 400 mm below atmospheric. The intensity of any pain produced was recorded on a VAS scale and electrodes were placed in both cavities in an attempt to monitor any action potentials evoked in intradental nerves. Results In all the teeth, the intensity of the pain produced by a stimulus tended to increase as the cavity was deepened, as did the number of action potentials recorded (in 6 of the 8 teeth). The responses were greater from etched than unetched dentine, and negative pressures evoked greater responses than the corresponding positive pressures. Conclusion There was no evidence that dentine close to the EDJ was more sensitive to hydrostatic pressure stimuli than deeper dentine. It may however be more sensitive to mechanical stimuli as it is more compliant.